2020
DOI: 10.5114/bta.2020.100420
|View full text |Cite
|
Sign up to set email alerts
|

Study of antioxidant activity of liposomal forms of quercetin and curcumin in ischemic heart disease

Abstract: Quercetin and curcumin are plant polyphenolic antioxidants with proven pharmacological efficacy. Their use is, however, limited due to low bioavailability and oral administration route. The encapsulation of lipophilic compounds in liposomes enables to increase their bioavailability and to create an injectable form. The present study aimed to comparatively investigate the antioxidant activity of a complex liposomal preparation containing two lipophilic antioxidants (quercetin and curcumin) and their monoprepara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Quercetin can improve the antioxidant ability of the ovary by up-regulating the oxidative stress-related genes in rat. 37 In addition, Quercetin activates the nuclear factor Nrf2-ARE (erythroid-derived 2) like 2/ Antioxidant response element path and induces the activity of phase II anti-oxidant enzymes like glutathione stransferase, catalase, superoxide dismutase, NAD(P)H: quinone oxidoreductase 1, glutathione peroxidase (GPx), and thioredoxin. 38 Data from the earlier studies showed quercetin's capacity to block the route of luteinizing hormone -derived androgen production.…”
Section: Discussionmentioning
confidence: 99%
“…Quercetin can improve the antioxidant ability of the ovary by up-regulating the oxidative stress-related genes in rat. 37 In addition, Quercetin activates the nuclear factor Nrf2-ARE (erythroid-derived 2) like 2/ Antioxidant response element path and induces the activity of phase II anti-oxidant enzymes like glutathione stransferase, catalase, superoxide dismutase, NAD(P)H: quinone oxidoreductase 1, glutathione peroxidase (GPx), and thioredoxin. 38 Data from the earlier studies showed quercetin's capacity to block the route of luteinizing hormone -derived androgen production.…”
Section: Discussionmentioning
confidence: 99%